Acceleration response modification factors for nonstructural components attached to inelastic moment-resisting frame structures. - Sankaranarayanan, Ragunath (Earthquake engineering & structural dynamics.)
A statistical analysis of the peak acceleration demands for nonstructural components (NSCs) supported on a variety of stiff and flexible inelastic regular moment-resisting frame structures with periods from 0.3 to 3.0 s exposed to 40 far-field ground motions is presented. Peak component acceleration (PCA) demands were quantified based on the floor response spectrum (FRS) method without considering dynamic interaction effects. This study evaluated the main factors that influence the amplification or decrease of FRS values caused by inelasticity in the primary structure in three distinct spectral regions namely long-period, fundamental-period, and short-period region. The amplification or decrease of peak elastic acceleration demands depends on the location of the NSC in the supporting structure, periods of the component and building, damping ratio of the component, and level of inelasticity of the supporting structure. While FRS values at the initial modal periods of the supporting structure are reduced due to inelastic action in the primary structure, the region between the modal periods experiences an increase in PCA demands. A parameter denoted as acceleration response modification factor (Racc) was proposed to quantify this reduction/increase in PCA demands.